SATB2 Is Superior to CDX2 in Distinguishing Signet Ring Cell Carcinoma of the Upper Gastrointestinal Tract and Lower Gastrointestinal Tract. (December 2018) - Ma, Changqing; Lowenthal, Brett M.; Pai, Reetesh K.
Abstract : Signet ring cell carcinomas of the gastrointestinal (GI) tract are clinically aggressive neoplasms with frequent intra-abdominal metastases at initial presentation. Currently available immunohistochemistry (IHC) markers cannot distinguish signet ring cell carcinomas of the lower GI tract and upper GI tract, suggesting the need for more specific diagnostic markers. SATB2 is a novel, sensitive marker for colorectal carcinoma. We hypothesized that SATB2 IHC can reliably identify primary and metastatic signet ring cell carcinomas of lower GI tract origin. SATB2 and CDX2 IHC was performed on 159 primary (n=93) and metastatic (n=66) signet ring cell carcinomas of GI tract origin and 13 metastatic breast carcinomas with signet ring cell features. Positive SATB2 expression (SATB2 + ) was identified in 82% (27/33) of appendiceal, 88% (43/49) of colorectal, 13% (7/54) of gastric, and 35% (8/23) of esophageal/esophagogastric junction signet ring cell carcinomas. Primary and metastatic signet ring cell carcinomas of lower GI tract origin were more frequently SATB2 + than those from upper GI tract (70/82, 85% vs. 15/77, 19%, P <0.01). Compared with CDX2, SATB2 + and dual-positive staining for SATB2 and CDX2 both had higher specificities for signet ring cell carcinomas from the lower GI tract (81% vs. 49% and 86% vs. 49%, respectively, P <0.01 for both). Two (15%) metastatic breast carcinoma were SATB2 +, but all 13 demonstrated negative CDX2 staining. In summary, our results show SATB2 is a relatively specific immunohistochemistry marker for both metastatic and primary signet ring cell carcinomas of lower GI tract origin.